Sequential experimentation for mixtures. (1st January 2012) - Weese, Maria L.; Leitnaker, Mary G.
We present a sequential method for experimenting with mixtures when the number of mixture components is large and the experimental goal is to gain information on a subset of components for the purpose of mixture product improvement. The model-independent method utilises parameter estimates from the Cox mixture model with a current product formulation from which to begin experimentation. The advantages of our method are the ability to perform experiments using a split-plot like structure and utilise it in a sequential manner on an operating process.